Elites in the UK: new approaches to contemporary class divisions - Ana Paula Hey (Tempo Social)
Abstract The aim of this article is to demonstrate the “new” elites emerging in the UK amidst the economic, political and social context of neoliberalism. To do this, we examine the works of Mike Savage regarding what elite studies have meant for contemporary forms of social division. Using data from the Great British Class Survey, the author underlines sociological elements that are central to the composition of this financialised elite. We describe cleavages in terms of social mobility, education, location and politicization that are generated through the concentration of distinct types of capital (economic, social and cultural). Departing from the specific context of Great Britain, we intend to contribute to the development of a sociology of elites, through a discussion of both new perspectives and the limits and possibilities of treating different geographic, political and social contexts.